Mathematical finance - Alhabeeb, M. J., 1954-; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
An introduction to the mathematical skills needed to understand finance and make better financial decisions Mathematical Finance enables readers to develop the mathematical skills needed to better understand and solve financial problems that arise in business, from small entrepreneurial operations to large corporations, and to also make better personal financial decisions. Despite the availability of automated tools to perform financial calculations, the author demonstrates that a basic grasp of the underlying mathematical formulas and tables is essential to truly understand finance. The boo.
Frontmatter -- Mathematical Introduction. Numbers, Exponents, and Logarithms -- Mathematical Progressions -- Statistical Measures -- Unit I Summary -- List of Formulas -- Exercises for Unit I -- Mathematics of the Time Value of Money. Introduction -- Simple Interest -- Bank Discount -- Compound Interest -- Annuities -- Unit II Summary -- List of Formulas -- Exercises for Unit II -- Mathematics of Debt and Leasing. Credit and Loans -- Mortgage Debt -- Leasing -- Unit III Summary -- List of Formulas -- Exercises for Unit III -- Mathematics of Capital Budgeting and Depreciation. Capital Budgeting -- Depreciation and Depletion -- Unit IV Summary -- List of Formulas -- Exercises for Unit IV -- Mathematics of the Break-Even Point and Leverage. Break-Even Analysis -- Leverage -- Unit V Summary -- List of Formulas -- Exercises for Unit V -- Mathematics of Investment. Stocks -- Bonds -- Mutual Funds -- Options -- Cost of Capital and Ratio Analysis -- Unit VI Summary -- List of Formulas -- Exercises for Unit VI -- Mathematics of Return and Risk. Measuring Return and Risk -- The Capital Asset Pricing Model (CAPM) -- Unit VII Summary -- List of Formulas -- Exercises for Unit VII -- Mathematics of Insurance. Life Annuities -- Life Insurance -- Property and Casualty Insurance -- Unit VIII Summary -- List of Formulas -- Exercises for Unit VIII -- References -- Appendix -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Finance -- Mathematical models; Investments -- Mathematics; Business mathematics; Finance -- Mathematical models; Investments -- Mathematics; Business mathematics; BUSINESS & ECONOMICS -- Finance; Business mathematics; Finance -- Mathematical models; Investments -- Mathematics; Electronic books